PENERAPAN PERMAINAN KIPPERS UNTUK MENINGKATKAN AKTIVITAS GERAK SISWA ( STUDI PADA SISWA KELAS IV B SD MENGANTI PERMAI GRESIK ) - O M O, T (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In the present, education is a very important thing in life weather it is for society, parent or children. But it is so wistful because people consider that education is not too important, whereas it is so necessary for everybody. Education has a very important role to progress a country, and to improve it more, it must be supported by the people. The purpose of the research is to know if the application of Kippers game can improve the students’ motion activity in thefourth grade elementary school students B in MengantiPermai Gresik. MengantiPermai Gresik is the location of this research with 25 students as the subject of the research. The application of Kippers game can improve the student’s motion activity. The research uses the action class research method or it is well-known as PTK that consists of some cycles of research started from pre-cycle until the third cycle. Based on the result of the research, the teachers are suggested to be able to see the expected result of the study and not give a difficult load for the students in learning and teaching process. The teacher can imply a little game to make the students enthusiastic, more active in moving and can improve their activity. From the whole result of the action class research, it can be concluded that the application of Kippers game in physical, physical exercise and health education in primary school of MengantiPermai Gresik is able to improve the students’ motion activity of the fourth grade primary school students B in MengantiPermai Gresik. Keywords : Application, Kippers game, the students’ motion activity.